Perancangan Aplikasi Sistem Parkir Otomatis menggunakan ERP Odoo Berbasis Internet of Things - Yusup Firmansyah; Rahmat Hidayat (SAINS DAN INFORMATIKA : RESEARCH OF SCIENCE AND INFORMATIC, 2021)
Universitas Singaperbangsa Karawang (UNSIKA) is a favorite Public universities in Karawang, West Java. UNSIKA parking system has not met the expectations of a good parking system, especially in the field of security. This research aims to solve the problem by designing an IoT-based automated parking system application with a high level of security, informative to provide comfort for users and managers. The method in the security system is to use barcodes and fingerprints, as for the application that will be made using ERP Odoo. The results of this study are a tool called BIOPARKS (Biometric Parking System) that can reduce the risk of theft in parking lots. Also, data management applications such as vehicle data, vehicle owner data, reports in and out of vehicles, as well as a monitor of parking conditions. The use of barcode and fingerprint technology in the parking system makes the security on the parking lot more secure so that the owner of the vehicle becomes calm. Applications designed to make data management more structured, as well as facilitate monitoring of parking conditions.